Impact of roasting temperature on the chemical composition and quality of avocado seed flour (Persea americana Mill.) - Novitasari, Rifni; Anggraini, Tuty; Hasbullah; Hervani, Dini (Jurnal Ilmiah Pertanian, 2025)
Avocado seeds (Persea americana Mill.) are an underutilized agricultural byproduct with significant starch content, making them a potential raw material for flour production. Roasting is a key processing method that enhances drying efficiency and improves sensory attributes. This study investigates the impact of roasting temperature (120°C, 130°C, 140°C, and 150°C) on the chemical composition and quality of avocado seed flour (ASF). The experiment was conducted using a Completely Randomized Design (CRD) with three replications. Proximate analysis and tannin content were determined through standard laboratory methods. Data were analyzed using analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test. The results indicate that the optimal roasting temperature for ASF is 150°C, yielding the following composition: moisture content (5.47±0.76%), tannin content (0.0723±0.0004%), protein content (1.66±0.033%), carbohydrate content (86.45±0.91%), fat content (2.08±0.23%), and ash content (4.34±0.03%). Higher roasting temperatures resulted in lower moisture and tannin levels, which are beneficial for improving ASF quality. This study provides valuable insights into optimizing roasting conditions for ASF production, enhancing its potential application in food processing.